The Influence Of Digital Comic-Based Instructional Media On Students' Narrative Text Writing Skills At SMP Muhammadiyah Rappang - Anita Candra Dewi; Erwin Eka Saputra; Usman; Baharman; Rahmat (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study investigates the influence of digital comic-based instructional media on students' narrative writing skills at SMP Muhammadiyah Rappang. The research aims to assess the effectiveness of digital comics in enhancing students' ability to construct well structured, coherent, and creative narrative texts. Method: A quasi experimental research design was applied, involving pre-test and post-test assessments of students' narrative writing skills. Data were collected through direct observations, student writing evaluations, and teacher feedback. The study measured improvements in key aspects of narrative writing, including structure, coherence, vocabulary use, and creativity. Results: The findings reveal that digital comic-based media significantly improve students' narrative writing skills compared to conventional teaching methods. Students exposed to digital comics demonstrated better organization of ideas, increased engagement in writing activities, and enhanced creativity in storytelling. However, several challenges were identified, including teachers' limited technological proficiency and restricted access to digital resources, which affected the optimal implementation of digital comics in the classroom. Novelty: This study highlights the potential of integrating digital comics into writing instruction to enhance student engagement and learning outcomes. It recommends the development of culturally relevant digital comics, increased teacher training in digital literacy, and improved technological infrastructure in schools. Additionally, strengthening pedagogical strategies for utilizing digital comics in writing instruction is crucial. These findings emphasize the importance of adopting innovative, visually engaging media to foster students' creativity and improve their writing proficiency in secondary education.